ENKRIPSI SMS (SHORT MESSAGE SERVICE) PADA TELEPON SELULAR BERBASIS ANDROID DENGAN METODE RC6 - Defni Defni; Indri Rahmayuni (Jurnal Momentum ISSN 1693-752X)
SMS (Short Message Service) is a service to send a sort message that many used in telephone, but in service of a SMS provider have infrequent method to make data of it be more secure, this making service of SMS have so many security gap that making data possibly lost or will be a third person who can access data of SMS. Android is a lateset mobile operating system from Google, android make programmer possibly develop the application easly to use in smartphone and tablet. Cybercryp SMS is an application that designed for android system that will use to secure data that use service of SMS. RC6 algorithm for encryption and decryption will be use in service of sender and receiver message from Short Message Service, that will use a private key and symmetric password for make data will be more secure and security gab can be resolved.